Physiological quality of barley seeds submitted to saline stress - Silva,Rodrigo Nascimento da (2007)
The objective of the experiments was to determine the influence of the effects of different salt levels (zero, 15, 30, 45 and 60mM NaCl) on the physiological quality of seeds of two barley cultivars (BRS 195 and AF 98067). Assays were conducted to evaluate salt stress on germination and vigor. The germination and germination rate of the barley seeds decreased as salt levels increased, reducing the seed viability and vigor. The salinity affected the membrane integrity, mainly in AF 98067 that showed more sensitivity to salt stress.